2009
DOI: 10.4992/jjpsy.80.33
|View full text |Cite
|
Sign up to set email alerts
|

Effects of neighborhood collective efficacy and violence on antisocial behavior: Dual mediation of socialization and routine activities

Abstract: The authors examined the e唖 ects of neighborhood collective e阿cacy and violence on adolescents' antisocial behavior tendencies by means of the dual mediation of socialization indices i.e., social information-processing and self regulation and routine activities. Collective e阿cacy and violence exposure were assessed by neighborhood "informal social control" and "social cohesion and trust" during the elementary and junior high school years, and the frequency of violence in the community during junior high and hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…Do you think it's OK for John to scream at him?” Responses are scored on a 4‐point scale, ranging from 4 ( Absolutely wrong ) to 1 ( Absolutely right ). The General Belief subscale consists of eight criteria, and again participants were asked how strongly they agreed with question such as, “In general, it is wrong to hit other people.” The Retaliation Belief subscale, which had lower predictive power for antisocial behaviors than other scales in a previous study (Yoshizawa et al, ), was omitted in the South Korean study, due to time restrictions on the survey permitted for this research. Scores for each criterion were averaged and reversed to create subscale scores of the questionnaire.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Do you think it's OK for John to scream at him?” Responses are scored on a 4‐point scale, ranging from 4 ( Absolutely wrong ) to 1 ( Absolutely right ). The General Belief subscale consists of eight criteria, and again participants were asked how strongly they agreed with question such as, “In general, it is wrong to hit other people.” The Retaliation Belief subscale, which had lower predictive power for antisocial behaviors than other scales in a previous study (Yoshizawa et al, ), was omitted in the South Korean study, due to time restrictions on the survey permitted for this research. Scores for each criterion were averaged and reversed to create subscale scores of the questionnaire.…”
Section: Methodsmentioning
confidence: 99%
“…Yoshizawa et al () analyzed the mediation model for Japanese participants using structural equation modeling and confirmed that the inhibitory effect of collective efficacy within communities on the experience of antisocial behaviors was mediated by the appropriateness of social information processing and social self‐regulation of youths. Social self‐regulation was defined as the ability to inhibit or to assert the self, depending on internal and external needs in a social setting when there is discrepancy between desire, intention, and current perception (Harada, Yoshizawa, & Yoshida, ).…”
Section: Neighborhood Factors and Antisocial Behaviorsmentioning
confidence: 95%
See 2 more Smart Citations
“…Cultural similarity is the key topic of the article entitled “Cross‐cultural Protective Effects of Neighborhood Collective Efficacy on Antisocial Behaviors: Mediating Role of Social Information Processing” by Yoshizawa et al (). Adolescent participants from 10 universities in Japan, China, South Korea, and the United States reported their collective efficacy, normative beliefs about aggression, and antisocial behavior.…”
mentioning
confidence: 99%